The Role of Muslim Chaplains in Higher Education: Should They Be Doing What They Are Doing? - Rajput, Asgar Halim (Practical theology, 2015)
Muslim chaplaincy in Britain is fairly new particularly in higher education. Currently there is no extensive study of what Muslim chaplains in higher education do and what the result of their actions is. With new legislation on Counter Terrorism and Security (CTS) imposed on universities and colleges, this article explores the role of Muslim chaplains in higher education, what they do and in evaluating what they do, identify certain valuable factors, for example if their role includes how they might support vulnerable students. This article first describes chaplaincy in general and then Muslim chaplaincy in higher education in particular, in order to find explanations for the purpose and role of Muslim chaplaincy in higher education. It then explores what Muslim chaplains might do and critically analyzes three areas to examine whether they might contribute towards the fuller, more appropriate development of the role of Muslim chaplaincy: Islamic tradition, Christian chaplaincy, and expectations of higher education. Finally, it reflects on the implications of these findings.